Generation and therapeutic efficacy of the novel Fc-modified cross-neutralizing human monoclonal antibodies against dengue virus - Subenya Injampa; Surachet Benjathummarak; Sujitra Keadsanti; Wilarat Puangmanee; Atsushi Yamanaka; Tadahiro Sasaki; Kazuyoshi Ikuta; Pongrama Ramasoota; Pannamthip Pitaksajjakul (bioRxiv (Cold Spring Harbor Laboratory), 2023)
Abstract Background: Dengue disease is a mosquito-borne infection caused by four dengue virus serotypes (DENV1–4). Secondary infections can produce flavivirus cross-reactive antibodies at sub-neutralizing levels. This phenomenon can significantly increase the severity of secondary infections via antibody-dependent enhancement (ADE). ADE activity is associated with a high risk of viral infection in immune effector cells, triggering cytokine cascade and activating the complement system, which lead to severe symptoms. Despite extensive studies, therapeutic antibodies, particularly fully human monoclonal antibodies, which can be an option for immune passive therapy, have not yet been discovered. Methodology/Principal Findings: This study generated LALA-mutated human monoclonal antibody clone B3B9 (LALA-B3B9 HuMAb) that can neutralize all four DENV serotypes without enhancing viral activity. The number of infected cells obtained with the ADE assay was compared among wild-type antibody (B3B9), and modified Fc, LALA-B3B9 HuMAb, and N297Q (N297Q-B3B9), with or without complement proteins. Moreover, the therapeutic efficacy of these HuMAbs against ADE infection by competing with natural antibodies in patients with acute dengue was determined using the in vitro suppression-of-enhancement assay in K562 cells. The novel Fc-modified antibody LALA-B3B9 (Leu234Ala/Leu235Ala mutations) could have a therapeutic effect. Further, it exhibited neutralization properties against all dengue virus serotypes without triggering ADE activity at any antibody concentration. This outcome was similar to that of the previous Fc-modified N297Q-B3B9 antibody (N297Q mutation). Moreover, the effect of complement protein on enhancing and neutralizing activities was evaluated to assess unwanted inflammatory responses to these therapeutic antibodies. Results showed that the elimination of complement activity could reduce the severity of dengue. The activities of LALA-B3B9 and N297Q-B3B9 HuMAbs were complement-independent in all dengue virus serotypes. Conclusions: LALA-B3B9 and N297Q-B3B9 HuMAbs can prevent the suppression-of-enhancement activity in K562 cells caused by human DENV2. Hence, they are promising candidates for dengue treatment. Author Summary Dengue is among the most important mosquito-borne infections that cause serious health issues in tropical and subtropical countries. There are no approved effective antiviral therapies available. The significant challenges for developing efficient therapeutic drugs include the presence of multiple serotypes and antibody-dependent enhancement. To overcome these issues, the LALA-mutated human monoclonal antibody clone B3B9 (LALA-B3B9) was generated. This antibody potently neutralizes all dengue virus serotypes and eliminates viral enhancement activity. Moreover, compared with the previous Fc-modified antibody clone N297Q-B3B9, LALA-B3B9 and N297Q-B3B9 HuMAbs do not activate the complement response, which is advantageous in reducing complement-mediated vascular leakage in vivo . In addition, they can compete with natural antibodies causing antibody-dependent enhancement in patients with acute dengue. Hence, LALA-B3B9 and N297Q-B3B9 HuMAbs have promising effects against dengue and can be further developed as a therapeutic drug in the future.
Keywords: Mosquito-borne diseases and control; Transgenic Plants and Applications; Insect symbiosis and bacterial influences